Pharmacy-based methadone dispensing and drive time to methadone treatment in five states within the United States: A cross-sectional study. (1st June 2020) - Joudrey, Paul J.; Chadi, Nicholas; Roy, Payel; Morford, Kenneth L.; Bach, Paxton; Kimmel, Simeon; Wang, Emily A.; Calcaterra, Susan L.
Highlights: There is a shortage of methadone dispensing facilities within the United States. Cross-sectional geospatial analysis of drive time to the nearest dispensing facility. Rural census tracts have disproportionately long drive times to methadone. This disparity could be mitigated by pharmacy-based methadone dispensing. Abstract: Background: Within the United States, there is a shortage of opioid treatment programs (OTPs), facilities which dispense methadone for opioid use disorder. It is unknown how pharmacy-based methadone dispensing, as available internationally, could affect methadone access. We aimed to compare drive times to the nearest OTP with drive times to the nearest chain pharmacy in urban and rural census tracts. Methods: Cross-sectional geospatial analysis of 2018 OTP location data and 2017 pharmacy location data. We included census tracts with non-zero population in Indiana, Kentucky, Ohio, Virginia, and West Virginia, states with highest rates of opioid overdose deaths. Our outcome was minimum drive time in minutes from census tract mean center of population to the nearest dispensing facility. Results: Among 7918 census tracts, median (IQR) drive time to OTPs increased from urban to increasingly rural census tract classification [16.1 min (10.2–25.9) to 48.4 min (34.0–63.3); p < .001]. Median (IQR) drive time to OTPs was greater than drive time to chain pharmacies among all census tracts: 19.6 min (11.6–35.1) versus 4.4 min (2.9–7.7) respectively; p < .001. The median (IQR) difference in drive time was greater for increasingly rural census tracts [11.5 min (6.1–19.2) to 35.2 min (19.6–49.7); p <.001] with pharmacy-based methadone dispensing. Conclusion: Rural census tracts have disproportionately long drive times to OTPs. Drawing from policies to increase methadone access in countries like Canada and Australia, this geographic methadone disparity could be mitigated through implementation of pharmacy-based methadone dispensing.